Local Government Response to Domestic Violence from Online Gambling: A Legal-Mashlahah Perspective - Anugerah, Ghifari Fajar; Hidayah, Khoirul; Lutfi, Mustafa (Al-Bayyinah, 2025)
This study aims to analyze the efforts of the Surabaya City Government in addressing domestic violence resulting from online gambling, using the perspectives of legal system theory and mashlahah. The focus of the research is on the role of the Surabaya City Office of Women’s Empowerment, Child Protection, Population Control, and Family Planning (DP3AP2KB) as the implementing agency for women and child protection policies. This study employs a qualitative approach, utilizing field studies and in-depth interviews with key informants from the agency, victims of domestic violence, and community leaders. The findings indicate that structurally, DP3AP2KB has undertaken several initiatives through socialization, education, and the provision of legal and psychological assistance for victims. However, the effectiveness of these policies is hindered by the community’s weak legal culture and limited public participation in prevention efforts. From the perspective of Lawrence M. Friedman’s legal system theory, the imbalance between structure, substance, and legal culture remains a major obstacle. Meanwhile, from a mashlahah perspective, the protection of victims and the prevention of domestic violence caused by online gambling are considered essential to preserving the well-being of families and society. Therefore, institutional synergy and the strengthening of legal literacy grounded in religious and social values are necessary to build an effective and sustainable protection system.